Low Incidence of Asymptomatic Positive Patients Detected During Preoperative Testing for Total Joint Arthroplasty During the COVID-19 Pandemic. Issue 23 (1st December 2021) - Zangrilli, Julian; Hameed, Daniel; Chisari, Emanuele; Vannello, Chris; Courtney, P. Maxwell; Krueger, Chad A.
Abstract : Introduction: Although the pause in elective surgery was necessary to preserve healthcare resources at the height of the novel coronavirus disease 2019 (COVID-19) pandemic, recent data have highlighted the worsening pain, decline in physical activity, and increase in anxiety among cancelled total hip and knee arthroplasty patients. The purpose of this study was to evaluate the effectiveness of our staged reopening protocol and the incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among elective arthroplasty patients. Methods: We identified all elective hip and knee arthroplasty patients who underwent our universal COVID-19 testing protocol during our phased reopening between May 1, 2020, and July 21, 2020, at our institution. We recorded the SARS-CoV-2 test results of each patient along with their demographics, medical comorbidities, and symptoms at the time of testing. We followed each of these positive patients through their rescheduled cases and recorded any complications or potential SARS-CoV-2 healthcare exposures. Results: Of the 2, 329 patients, we identified five patients (0.21%) with a reverse transcription-polymerase chain reaction–confirmed SARS-CoV-2 positive test, none with symptoms. All patients were successfully rescheduled and underwent their elective arthroplasty procedure within 6 weeks of their original surgery date. None of these patients experienced a perioperative complication at the time of their rescheduled arthroplasty procedure. No orthopaedic surgeon or staff member caring for these patients reported a positive SARS-CoV-2 test. Conclusion: Our phased reopening protocol with universal preoperative virus testing was safe and identified a low incidence of SARS-CoV-2 among asymptomatic, elective arthroplasty patients at our institution. With uncertainty regarding the trajectory of the COVID-19 pandemic, we hope that this research can guide future policy decisions regarding elective surgery.